Results of long-term follow-up after catheter ablation of atrial fibrillation. (22nd September 2015) - Berriman, TJ; Hunter, RJ; Thomas, G; Kamdar, R; Richmond, L; Baker, V; Dhinoja, M; Abrams, D; Earley, MJ; Sporton, S; Schilling, RJ
Abstract : Background: Published long-term follow-up data for catheter ablation of atrial fibrillation (AF) are scarce. We present the long-term follow-up of patients undergoing an identical AF ablation procedure. Methods: We began performing wide area circumferential ablation (WACA) with confirmation of electrical isolation in July 2001. Procedural outcomes and follow-up were collected prospectively. We also attempted to contact all patients undergoing ablation up until March 2008 for an updated follow-up. Patients were contacted by telephone to review symptoms, confirm complications, medications and arrange an ECG through local doctors. Results: 469 procedures occurred in 286 patients. The mean age was 57 ± 11 years, 74% were men, 25% had structural heart disease and 55% paroxysmal AF. 149 patients had one procedure, 102 had two, 25 had three, nine had four and one had five (mean 1.6 per patient). First-time procedures took 240 ± 9 minutes (201 ± 58 paroxysmal vs 287 ± 98 persistent, p<0.001), with fluoroscopy time of 52 ± 31 minutes (47 ± 33 vs 59 ± 27, p<0.01). Complications were: transient ischaemic attack/cerebrovascular accident in 0.7%, pericardial effusion in 2.4% (1.3% required drainage, surgically in one case), re-attendance with bruising or haematoma 16% (0.3% required transfusion) and clinically insignificant pulmonary vein stenosis in 0.9%. Median follow-up from first procedure was 550 days (range 122–2115 days). Of the original 286 patients, three had died and 10 could not be traced. Of the remaining 273 patients, 198 had ECG. 66% remained free from symptoms attributable to AF, 9% had minimal palpitations defined as less than 1 minute per week, 25% still had regular palpitations, although improved symptomatically, 2% said they were unchanged and 0.4% felt worse (97% improved or AF free). 82% were in sinus rhythm (90% paroxysmal, 71% persistent). 69% were no longer taking any antiarrhythmic drugs. For those who remained symptom free at 2 years, there was no further recurrence of AF. Conclusion: These data add to the small body of literature examining the long-term efficacy of catheter ablation of AF. This study shows that AF ablation is effective in the long term and that complications are low. Freedom from AF at 2 years predicts long-term cure.